2000
DOI: 10.1007/s002530050013
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of pentachlorophenol with laccase from Coriolus versicolor

Abstract: Laccase, purified from Coriolus versicolor, removed pentachlorophenol (PCP) from solution at pH 5, depending on initial PCP concentration and amount of laccase. With 100 units of laccase, 100% of 25 microg ml(-1) PCP and 60% of 200 microg ml(-1) PCP were removed respectively over 72 h. No free chloride was released in the reaction. In reaction with 100 microg PCP, products were primarily polymers (about 80,000 MW) with only 2-3 pg of o- and p-chloranils formed. Polymers were stable to acid hydrolysis and no re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(45 citation statements)
references
References 14 publications
3
40
0
2
Order By: Relevance
“…The results suggested the relevance of the enzymatic levels, especially for the peroxidases present in the inoculum soon after its inoculation in the soil on the quality of the inoculum to be employed. The capacity of basidiomycetes to degrade chlorophenols, including pentachlorophenol as already reported in literature (Okeke et al 1997;Ullah et al 2000;Seradati et al 2003;Machado et al 2005a;Soares et al 2011) was proved here. There are difficulties to use the concentrations above 200 mg kg -1 pentachlorophenol, given the basidiomycetes' sensibility to the pollutant (Leontievsky et al 2001;Ahn et al 2002;Walter et al 2004).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The results suggested the relevance of the enzymatic levels, especially for the peroxidases present in the inoculum soon after its inoculation in the soil on the quality of the inoculum to be employed. The capacity of basidiomycetes to degrade chlorophenols, including pentachlorophenol as already reported in literature (Okeke et al 1997;Ullah et al 2000;Seradati et al 2003;Machado et al 2005a;Soares et al 2011) was proved here. There are difficulties to use the concentrations above 200 mg kg -1 pentachlorophenol, given the basidiomycetes' sensibility to the pollutant (Leontievsky et al 2001;Ahn et al 2002;Walter et al 2004).…”
Section: Discussionsupporting
confidence: 50%
“…min -1 ). The detection was made at 254 nm; pentachlorophenol retention time in the chromatographic column was between 7 and 7.4 min after sample injection (Ullah et al 2000). The pentachlorophenol amount from the extracts was estimated after a previously settled standard curve, where the amounts found were obtained linearregression analysis (y = 6000000x + 92782; r 2 = 0.999).…”
Section: Pentachlorophenol Quantificationmentioning
confidence: 99%
“…Notably, similar to this study, Jeon et al (2008) observed poor degradation of pentachlorophenol by laccase (from Ganoderma lucidum). Conversely, Ullah et al (2000) reported complete degradation of pentachlorophenol by laccase (from Coriolus versicolor). This contradiction may be explained by the difference in ORP of laccase derived from different sources (Xu et al, 2000).…”
Section: Troc Degradation Capacity Of the Laccase Utilizedmentioning
confidence: 99%
“…Laccases catalyze the removal of a hydrogen atom from phenolic substrates and aromatic amines by one-electron abstraction. The free radicals formed during the reaction are also capable of undergoing further depolymerization, repolymerization, demethylation or quinone formation [2][3][4]. The low substrate specificity of laccases and their ability to oxidize many pollutants suggest their industrial and biotech-nological applications [5,6].…”
Section: Introductionmentioning
confidence: 99%